2017
DOI: 10.1186/s13052-017-0351-2
|View full text |Cite
|
Sign up to set email alerts
|

Lung structure and function similarities between primary ciliary dyskinesia and mild cystic fibrosis: a pilot study

Abstract: BackgroundPrimary ciliary dyskinesia (PCD) and cystic fibrosis (CF) are increasingly compared. There are no chest magnetic resonance imaging (MRI) comparative studies of PCD and CF. We assessed clinical, functional, microbiological and MRI findings in PCD and mild CF patients in order to evaluate different expression of lung disease.MethodsTwenty PCD (15.1 years) and 20 CF subjects with mild respiratory impairment (16 years, 70% with pancreatic insufficiency) underwent MRI, spirometry, and sputum cultures when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…Comparisons of lung function between PCD and CF are rare and the results have been unclear. Some studies concluded that FEV1 was similar in PCD and CF patients [31,40,41], while another reported that it was lower in PCD children compared to pancreatic-sufficient and -insufficient CF children [42]. Yet another study found that children with PCD had better FVC, but similar FEV1 to children with CF [43].…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of lung function between PCD and CF are rare and the results have been unclear. Some studies concluded that FEV1 was similar in PCD and CF patients [31,40,41], while another reported that it was lower in PCD children compared to pancreatic-sufficient and -insufficient CF children [42]. Yet another study found that children with PCD had better FVC, but similar FEV1 to children with CF [43].…”
Section: Discussionmentioning
confidence: 99%
“…The structural changes seen on pulmonary CT scans from patients with Cystic Fibrosis (CF) and Primary Ciliary Dyskinesia (PCD), both causes of significant bronchiectasis, have been the basis of numerous previous reports [ 1 6 ]. More information on the range of these structural changes is available from patients with CF, due in part to the ability to detect CF by new born screening and because early treatment of this common genetic disease has the potential to prevent or retard the onset of bronchiectasis.…”
Section: Structural Lung Disease In Pcd – Is the Use Of Cf Derived Scmentioning
confidence: 99%
“…PCD is an important cause of bronchiectasis and there are several reports that describe the radiological features of PCD-bronchiectasis [ 2 6 , 8 ]. Most groups have used CF derived, scoring systems to describe these changes.…”
Section: Structural Lung Disease In Pcd – Is the Use Of Cf Derived Scmentioning
confidence: 99%
“…Although computed tomography (CT) imaging has been used clinically in cystic fibrosis, studies reporting changes in PCD with specific relationships between structural and functional abnormalities are lacking. However, there is some evidence of similar magnetic resonance imaging (MRI) and lung function changes in PCD and cystic fibrosis subjects with mild pulmonary disease [13]. Inclusion of CT imaging and MRI is being encouraged in randomised controlled interventional trials in cystic fibrosis to allow improved assessments of cystic fibrosis disease progression [14].…”
mentioning
confidence: 99%